2011
DOI: 10.1111/j.1365-246x.2011.05105.x
|View full text |Cite
|
Sign up to set email alerts
|

A marine electromagnetic survey to detect gas hydrate at Hydrate Ridge, Oregon

Abstract: S U M M A R YGas hydrates are a potential energy resource and hazard for drilling and infrastructure, yet estimates of global volume vary by over three orders of magnitude. Hydrates are electrically resistive compared to water saturated sediment and so electromagnetic methods provide an additional tool to seismic surveys and drilling for determining hydrate saturations. A marine electromagnetic survey was carried out at Hydrate Ridge, Oregon, USA, with the aim of testing the use of controlled source electromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 75 publications
(107 reference statements)
2
38
0
Order By: Relevance
“…The comparison can be limited further to resistivities in areas of hydrate presence derived from CSEM studies only for a like-to-like comparison. Resistivities of 3-12 m in the Hikurangi Margin, offshore New Zealand (Schwalenberg et al 2010a), around 4 m in Porangahau Ridge, offshore New Zealand (Schwalenberg et al 2010b), 3-5 m in the Cascadia margin (Schwalenberg et al 2005), and no greater than 5 m for the Hydrate Ridge (Weitemeyer et al 2006b(Weitemeyer et al , 2011 were reported, which are comparable to the values of resistivity reported here. These sites, however, were all in deeper water, with a more distal sediment supply without any glaciogenic component.…”
Section: Interpretation Of Resistivity Modelssupporting
confidence: 75%
See 1 more Smart Citation
“…The comparison can be limited further to resistivities in areas of hydrate presence derived from CSEM studies only for a like-to-like comparison. Resistivities of 3-12 m in the Hikurangi Margin, offshore New Zealand (Schwalenberg et al 2010a), around 4 m in Porangahau Ridge, offshore New Zealand (Schwalenberg et al 2010b), 3-5 m in the Cascadia margin (Schwalenberg et al 2005), and no greater than 5 m for the Hydrate Ridge (Weitemeyer et al 2006b(Weitemeyer et al , 2011 were reported, which are comparable to the values of resistivity reported here. These sites, however, were all in deeper water, with a more distal sediment supply without any glaciogenic component.…”
Section: Interpretation Of Resistivity Modelssupporting
confidence: 75%
“…The use of marine CSEM for hydrate detection was first suggested by Edwards (1997) and has been successful in various academic studies (e.g. Schwalenberg et al 2005;Weitemeyer et al 2006a;Schwalenberg et al 2010a,b;Weitemeyer & Constable 2010;Weitemeyer et al 2011;Goswami et al 2015;Attias et al 2016). It was also used commercially in Japan for hydrate exploration (referenced within Constable et al (2016)).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated that by using various synthetic inversions we were able to determine both the horizontal and depth sensitivity of the inversions, as well as distinguish between real resistive anomalies and those that are artefacts which appear beneath the CNEO3 pockmark. The magnitude of the main resistivity anomaly (>3 Ωm) beneath CNE03 that emerged from our inversions is consistent with the magnitudes found in other gas hydrate exploration studies (Schwalenberg et al 2005(Schwalenberg et al , 2010Weitemeyer et al 2011;Sun et al 2012).…”
Section: 1supporting
confidence: 79%
“…The recent upsurge in mCSEM applications for hydrocarbon exploration has led to intensive research and knowledge generation, including insights from synthetic studies (Weiss and Constable, 2006;Um and Alumbaugh, 2007;Commer and Newman, 2008;Sasaki and Meju, 2009) as well as real data inversions (e.g., Newman et al, 2010;Schwalenberg et al, 2010;Li et al, 2011;Weitemeyer et al, 2011;Súilleabháin et al, 2012). Whereas the physics of the method is the same for surveys on land, inversion of land CSEM data poses several challenges not equally encountered in mCSEM.…”
Section: Introductionmentioning
confidence: 99%